Between demarcation and discretion: The medical-administrative boundary as a locus of safety in high-volume organisational routines. (April 2018) - Grant, Suzanne; Guthrie, Bruce
Abstract: Patient safety is an increasing concern for health systems internationally. The majority of administrative work in UK general practice takes place in the context of organisational routines such as repeat prescribing and test results handling, where high workloads and increased clinician dependency on administrative staff have been identified as an emerging safety issue. Despite this trend, most research to date has focused on the redistribution of the clinical workload between doctors, nurses and allied health professionals within individual care settings. Drawing on Strauss's negotiated order perspective, we examine ethnographically the achievement of safety across the medical-administrative boundary in key high-volume routines in UK general practice. We focus on two main issues. First, GPs engaged in strategies of demarcation by defining receptionist work as routine, unspecialised and dependent upon GP clinical knowledge and oversight as the safety net to deal with complexity and risk. Receptionists consented to this 'social closure' when describing their role, thus reinforcing the underlying inter-occupational relationship of medical domination. Second, in everyday practice, GPs and receptionists engaged in informal boundary-blurring to safely accommodate the complexity of everyday high-volume routine work. This comprised additional informal discretionary spaces for receptionist decision-making and action that went beyond the routine safety work formally assigned to them. New restratified intra-occupational hierarchies were also being created between receptionists based on the complexity of the safety work that they were authorised to do at practice level, with specialised roles constituting a new form of administrative 'professional project'. The article advances negotiated order theory by providing an in-depth examination of the ways in which medical-administrative boundary-making and boundary-blurring constitute distinct modes of safety in high-volume routines. It also provides the basis for further research and safety improvement to maximise team-level understandings of the pivotal role of medical-administrative negotiations in achieving safety and mitigating risk. Highlights: The medical-administrative boundary is a key locus of safety in primary care. The GP safety net is defined in terms of the clinical oversight of receptionist work as a form of boundary-making. GPs increasingly rely on a receptionist safety net for the filtering of routine and complex work. Informal boundary-blurring is a key dimension of receptionist safety work. Receptionist boundary-blurring occurs in discretionary spaces within routine work.